Effect of bleaching on microhardness of two nanofilled and one microhybrid composite resins - Farinaz Shirban; Mohammad Hosein Fathi; Vajihesadat Mortazavi; Mohammad Reza Shirban (Isfahan University of Medical Sciences, 2011)
Introduction: Discolored teeth can be treated by various techniques, including direct composite resin veneers, indirect porcelain veneers, ceramic crowns and bleaching agents. The aim of this study was to evaluate the effect of at-home and in-office bleaching agents on the surface microhardness of one microhybrid (Point 4) and two nanofilled (Filtek Supreme and Premise) composite resins.Materials and methods: Opalescence PF with 20% carbamide peroxide and Opalescence Quick with 35% carbamide peroxide were used as at-home and in-office bleaching agents, respectively. Fifty samples from each composite resin, including Point 4 microhybrid, Premise and Filtek Supreme nanofilled composites resins were prepared and exposed to bleaching agents. For each composite resin the samples were randomly divided into five groups of 10 and designated as: control, two-week at-home, four-week at-home, one-time in-office and two-times in-office bleaching groups with two-week intervals. After the appropriate bleaching procedures on samples of each group, microhardness measurements were carried out on each sample. Data was analyzed using ANOVA and post hoc Tukey HSD test (p value < 0.05).Results: There were significant differences in mean surface microhardness values of each composite resin type. No significant differences were observed in mean microhardness values of Point 4 between four-week at-home and one-time office, Filtek Supreme between two-week at-home and four-week at-home, and Premise between one-time in-office and two-time in-office bleaching groups.Conclusion: Under the limitations of the present study, it was concluded that the microhardness of three composite resins tested in the present study were affected by bleaching agents. Key words: Bleaching, Microfilled composite resin, Nanofilled composite resin, Surface microhardness.